Cohesive devices in argumentative essays by Indonesian EFL learners - Meyga Agustia Nindya; Utami Widiati (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2020)
Cohesive devices are essential elements that have long been recognized as important features of good writing. However, making use of them appropriately is viewed as problematic for learners. This descriptive qualitative study aimed to investigate Indonesian EFL learners' ability to use cohesive devices in their writings. Twenty EFL learners of a state university in Malang, East Java, Indonesia were required to write and send one piece of argumentative essay consisting of five paragraphs to be analyzed. Twenty essays were analyzed by identifying the number of correct and errors of grammatical cohesion. The errors were then evaluated to know the possible causes that contributed to the learners' errors. The results showed that the total number of grammatical cohesion used by the learners was 2386, while 175 of them performed errors. It was also found that there was a heavy reliance on the use of particular cohesive items. The intralingual transfer mostly caused the errors made by learners. This implied a need for writing teachers to apply strategies for the development of EFL learners' writing ability, such as exposing students to exercises, using collaborative learning, giving feedback, and using the learning management system.